EFEKTIFITAS IKLAN MEDIA BALIHO PT KENCANA MAJU BERSAMA TERHADAP BRAND AWARENESS CABANG SURABAYA - fisa, esterer (Sintesa, 2024)
PT Kencana Maju Bersama chose billboard advertising media to market its products. It is known that the way to promote this product is by advertising through billboards which have been designed with the characteristic red color, boomerang logo, and also the slogan "no tricks". Considering that the expenditure associated with displaying billboards is so large, this makes researchers aim to conduct research on the effectiveness of Kencana billboard advertising on brand awareness in the surrounding community. The theory used in this research is media exposure. A quantitative method approach and quantitative descriptive research were used to distribute questionnaires around the area, and the sample in this research was all people with an age range of 20-60 years with a total of 100 respondents. The technique for collecting data is through calculating CRI and Brand Awareness indicators by distributing questionnaires to the surrounding community and also via social media for respondents. This research shows the results of the effectiveness of PT Kencana Maju Bersama's billboard media advertising on Brand Awareness in the Surabaya branch area which has an influence in creating brand awareness value of 62.3% with the results of this research showing that Ha is accepted while Ho is rejected. The t value is 7.887 with a significance level of 0.001 ≤ 0.1. This means that advertising on billboard media marketed by PT Kencana Maju Bersama can be said to be effective. It is hoped that the results of this research can be used as additional knowledge or guidance to support future research, especially those studying communication science, interested in knowing the impact of using billboard advertising or advertising media using the CRI, Media Exposure, and Brand Awareness methods or other methods as a means of promotion by companies that want to increase consumer brand awareness. Keywords: Effectiveness, Advertising, Billboard media, Brand awareness